De los Derechos Humanos: Reimagining Civics in Bilingual & Bicultural Settings. Issue 1 (2nd January 2017) - Gibson, Melissa Leigh
ABSTRACT: Dominant approaches to teaching social studies often marginalize bilingual and bicultural students. This is particularly troubling because the explicit goal of the social studies is to cultivate civic participation. Educational inequalities are thus tied to political inequalities. In light of this, this article shares a narrative case study of the author's own bilingual and bicultural approach to teaching middle school civics at a dual-language American school in Mexico. Through the illustration of a comparative civics curriculum that incorporates translanguaging practices, the author argues that embracing bilingualism and biculturalism in the social studies can lead to more expansive possibilities for justice-oriented civic education.